Minimalisasi penyebaran Covid - 19 di Kantor Pelayanan Desa Mojokrapak Melalui Kegiatan Pengabdian Pembuatan Hand Sanitizer - Waslah Waslah; Ani Safiriya A; Ahmad Fawaid Zuhri (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Community service activities carried out in the krapak hamlet, Mojokrapak village, Tembelang Jombang, aimed to provide knowledge about training in making handsanitizer tools in the midst of the covid 19 pandemic. It was carried out because of the situation. For many people come to the Tembelang Village Service Office for certain purposes so that the use of hand sanitizer will occur. This community service activity is carried out by means of lectures, discussions and demonstrations. This training on making hand sanitizer tools aims to increase public awareness of the importance of complying with health protocols and can minimize the spread of covid-19 and minimize the occurrence of crowds in services and optimizing village government services to the community